PENGARUH FREKUENSI DAN WAKTU PENCUCIAN BERBANTU ULTRASONIK MENGGUNAKAN ISOPROPANOL TERHADAP KADAR GLUKOMANAN DAN VISKOSITAS TEPUNG PORANG (Amorphophallus oncophyllus) - Lucia Hermawati Rahayu; Dyah Hesti Wardhani; Abdullah Abdullah (METANA, 2014)
Abstract Konjac (Amorphophallus oncophillus) contains a  high economic value of soluble fiber glucomannan. Most of Indonesia konjac flour is exported in  low  (glucomannan content <65) hence  sell in cheap price. Quality of glucomannan could be improved by removing impurities such as starch and cellulose.  Application of              ultrasonic-assisted extraction (leaching) of non glucomannan compound is an effective  method to purify the konjac flour. The purpose of this study was to study the effect of  ultrasonic waves frequency and leaching time of   ultrasonic-assisted extraction method using aqueous isopropanol on glucomannan purification. The leaching conducted two frequencies  (20 and 40 kHz) and various extraction time (5, 10, 15, 20, 25 minutes). The results showed that the best condition  of glucomannan purification was achieved at  20 kHz for 10 minutes. In this conditon, glucomannan content , viscosity and yield were 76.1%,  12,800 cPs, and 96.1%, respectively. Keywords: konjac (Amorphophallus oncophillus), glucomannan, ultrasonic-assisted extraction, isopropanol